State intervention and economic growth in Southern Italy: the rise and fall of the 'Cassa per il Mezzogiorno' (1950–1986). Issue 3 (3rd April 2017) - Felice, Emanuele; Lepore, Amedeo
Abstract: In the second half of the twentieth century, the Italian government carried out a massive regional policy in southern Italy, through the State-owned agency 'Cassa per il Mezzogiorno' (1950–1986). The article reconstructs the activities of this agency, making use of its yearly reports and of national and local archives. The Cassa was effective in the first two decades, thanks to substantial technical autonomy and, in the 1960s, to a strong focus on industrial development; however, from the 1970s it progressively became an instrument of waste and misallocation. At the local level, we find significant differences between the southern regions, and correspondence between the quality of state intervention and the regional patterns of GDP and productivity.